Ephemeral Mediterranean Watercourses Strongly Altered by Growth in Tourism: The Case of Benidorm (Spain) - Estela García-Botella; Alfredo Ramón-Morte (Geosciences, 2023)
Many ephemeral Mediterranean watercourses are affected by the growth of tourism and the demand for holiday homes. Calculating the runoff threshold in these small basins is vital for understanding the impact generated by urban growth and its incidence on the increase in flood hazards. The reconstruction of paleochannels, as well as appropriate scalar analysis and the use of geographical information variables, are fundamental for the correct estimation of flood risk and the implementation of coherent territorial planning policies. This case study of the Barceló ravine in the city of Benidorm, Spain, demonstrates the importance of the correct and complementary use of official, standardised, and open databases. The correct use of these geoinformation repositories, together with the fieldwork and historical reconstruction of paleofloods, form the set of strategic information variables for the study of flooding in these altered and dangerous watercourses that affect touristic urban zones around the Mediterranean.